Investigating Students’ Academic Performance as Mediated by Students’ Academic Ambition and Effort in the Public Senior High Schools in Ashanti Mampong Municipality of Ghana - Ampofo, Eric Twum; Osei-Owusu, Benedict (Selected Topics in Humanities and Social Sciences Vol. 7, 2021)
The purpose of this study was to investigate how some key variables influence and mediate the academic performance of SHS students in Ghana's Ashanti Mampong Municipality. The data was collected via questionnaires and descriptive and correlational research techniques were applied. A multi-stage sampling technique yielded a sample size of 571 pupils. The findings of the study established father’s education, mother’s education, the child’s academic ambition and the child’s effort as the associates of academic performance. The data also demonstrated that academic achievement is mostly influenced by the mother's education, sex of the child, the child's academic ambition, and the child's effort. The results failed to reject the null hypothesis once more. Based on these findings, it was suggested that educational stakeholders must instil high academic ambition in students, and that parents should ensure that a significant portion of their children's time is spent on their books, and that they should be prepared to help their children when the going gets tough.